Perspectives on Disabilities in Sierra Leone. (November 2022) - Morin, Kristi L.; Tomaszewski, Brianne R.; Bauer, Kathleen; Blasko, Alyssa M.; Enriquez, Grace B.; Tasik, Emily J.; Mehta, Khanjan
Most disability research originates from high-income countries, masking important cultural variability in how disability is conceptualized. Through 199 interviews with people living in Sierra Leone, we investigated the following research questions: (1) What are the experiences of community members with people with disabilities? (2) What employment options or other resources are available for people with disabilities? (3) How do community members perceive people with disabilities? We used a mixed-method approach to data analysis by quantitizing the qualitative responses to further examine whether participants' responses differed by urbanicity, age, or level of education. The results of this study provide insight into how disability is understood in a low-income country and reveal important directions for future research.